A N-phosphinoamidinato NHC-diborene catalyst for hydroboration - Fan, Jun (2021)
The use of the N-phosphinoamidinato NHC-diborene catalyst 2 for hydroboration is described. The N-phosphinoamidine tBu2PN(H)C(Ph)═N(2,6-iPr2C6H3) was reacted with nBuLi in Et2O to afford the lithium derivative, which was then treated with B2Br4(SMe2)2 in toluene to form the N-phosphinoamidinate-bridged diborane 1. It was reacted with the N-heterocyclic carbene IMe (:C{N(CH3)C(CH3)}2) and excess potassium graphite at room temperature in toluene to give the N-phosphinoamidinato NHC-diborene compound 2. It can stoichiometrically activate ammonia-borane and carbon dioxide. It also showed catalytic capability. A 2 mol % portion of 2 catalyzed the hydroboration of carbon dioxide (CO2) with pinacolborane (HBpin) in deuterated benzene (C6D6) at 110 °C (conversion >99%), which afforded the methoxyborane [pinBOMe] (yield 97.8%, TOF 33.3 h-1) and the bis(boryl) oxide [(pinB)2O]. In addition, 5 mol % of 2 catalyzed the N-formylation of secondary and primary amines by carbon dioxide and pinacolborane to yield the N-formamides (average yield 91.6%, TOF 25.9 h-1). Moreover, 2 showed chemoselectivity toward catalytic hydroboration of carbonyl compounds. In mechanistic studies, the B═B double bond in compound 2 activated the substrates, the intermediates of which then underwent hydroboration with pinacolborane to yield the products and regenerate catalyst 2.